Can the Technological Advancement Eliminate the Human Aspect of Human Resources Management? - Shammout, Marwan Mustafa (International Journal of Membrane Science and Technology, 2023)
This study attempts to answer the question, “Can technological advancement eliminate the human aspect in human resources management?” using different comparisons and highlighting several aspects of HRM while shedding light on the relationship between HRM (Human Resources Management) and AI (Artificial Intelligence). In addition to a wealthy literature review that states the various viewpoints on the subject and how such a collaboration between the two majors can lead to significant positive outcomes while considering the potential drawbacks.